RNA Interference in Insects: Protecting Beneficials and Controlling Pests - Vogel, Elise; Santos, Dulce; Mingels, Lina; Verdonckt, Thomas-Wolf; Broeck, Jozef Vanden (Frontiers in Physiology, 2019)
Insects constitute the largest and most diverse group of animals on Earth, with a matching virome diversity. RNA(i) interference is a post transcriptional gene silencing mechanism mediated by small RNA molecules and constitutes the main antiviral immune mechanism in this group of animals. Furthermore, this process can be artificially triggered via delivery of gene-specific double-stranded RNA molecules, leading to specific endogenous gene silencing. This is called RNAi technology and has important applications in several fields. In this paper, we start by reviewing the mechanisms of RNAi in insects as well as the potential of the RNAi technology to contribute to species-specific insecticidal strategies. We cover the range of strategies considered and investigated so far, as well as their limitations and the most promising approaches to overcome them. Next, we discuss patterns of viral infection, as well as review persistent and acute insect viral infections. Regarding the latter, a special focus is put on the ones affecting economically relevant species. In this scope, the use insect-specific viruses as bio-insecticides is likewise reviewed. In a third section, RNAi-based strategies to protect beneficial insects from harmful viral infections are explained and their potential practical application is discussed. As a whole, this manuscript stresses the impact of insect viruses and RNAi technology in human life. In addition, it points towards clear lines of investigation within an exciting and promising field of research.